Is one-time carbon monoxide intoxication harmless? Evaluation by argyrophilic nucleolar-organizing regions staining method. (January 2015) - Çolakoğlu, S; Saritas, A; Eroz, R; Oktay, M; Yaykasli, KO; Akoz, A; Kaya, E; Kandis, H
In carbon monoxide (CO) poisoning, CO affects the oxygen-carrying capacity of the hemoglobin molecule. Nucleolar-organizing regions (NORs) are genetic loci on chromosomes that are composed of ribosomal DNA and proteins. NORs can be stained with silver. A total of 18 rats were exposed to CO in three different concentrations (1000, 3000, and 5000 ppm) with 6 rats as controls. The animals were euthanized 7 days after CO intoxication. Lung tissues were taken, embedded in paraffin blocks, and sectioned at 5 μm thickness. Argyrophilic nucleolar-organizing region (AgNOR) staining was carried out. One hundred nuclei per individual were evaluated, and total AgNOR number per total nuclear number and total AgNOR area per nuclear area (TAA/NA) for each nucleus were analyzed. The CO exposure groups had significantly higher TAA/NA values and AgNOR numbers than the control group ( p < 0.05). Although the differences between 1000 ppm and the other two CO-exposed groups were meaningful ( p < 0.05) in the TAA/NA values, there were no differences among the CO exposure groups for the AgNOR number ( p > 0.05). The increase in TAA/NA value depends on the increase in the CO exposure. Significant correlations between both the AgNOR values and histopathological scoring methods were found. Therefore, AgNOR staining method may be used as an indirect indicator for evaluating the degree of cell damage rate.